RESPON INDONESIA TERHADAP KEBIJAKAN ORGANISASI MELANESIAN SPEARHEAD GROUP - Sinka Ernes Milanova; Umi Oktyari Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The protracted conflict for Free Papua has become a problem that has not been resolved until now. This separatist movement greatly disturbed Indonesian sovereignty. Indonesia is trying to solve problems safely, peacefully, and effectively, one of which is by joining the Melanesian Spearhead Group. This study discusses the influence and how Indonesia's steps change its status from observer to associate member at the MSG. To provide more specific accuracy to the results, researchers use the liberalism paradigm and diplomacy theory as a primary reference for research to clarify the effect of changes in Indonesia's status on MSG foreign policy on the issue of an independent Papua and steps to change Indonesia's position in the MSG. The analysis was carried out by analyzing documents, books, officially published journals, news, and Twitter. The results showed that changes in Indonesia's membership status from observer to associated member led to changes in the dynamics of foreign policy taken by the Melanesian Spearhead Group organization due to differences in rights and obligations held in each position in the Melanesian Spearhead Group. Associate member status allows Indonesia to provide foreign assistance regarding social and economic aspects, weakening their movement and intervention. Disagreements and conflicts among members have caused the agenda for an independent Papua to no longer be the main agenda in MSG discussions. Keywords: Separatism, Free Papua, International Organization, Melanesian Spearhead Group.